Theoretical Concepts - Tuomela, R. author. aut Link
1 illus.
Keywords: to that goal, and it is hoped that it will incorporate further works dealing in an exact way with interesting philosophical issues. Zurich, April 1973 Mario Bunge Preface In this book I have investigated the logical and methodological role of the much debated theoretical concepts in scientific theories. The philosophical viewpoint underlying my argumentation is critical scientific realism. My method of exposition has been to express ideas first in general terms and then to develop and elaborate them within a specific formal framework. It is assumed in the book that the reader has a relatively good knowledge of the basic techniques and results of modern symbolic logic, including model theory. Examples from actual science are mostly from the social sciences. I have deliberately omitted a treatment of a number of characteristic features which are particular to theoretical concepts in the more developed sciences, such as modern physics. This book owes very much to Professor Jaakko Hintikka, to whom I wish to express my deep gratitude. Especially at the begin ning of this project in 1968/69 when I was doing research for my doctoral degree at Stanford University I worked with him closely.